2011
DOI: 10.1121/1.3575599
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition in noise with active and passive hearing protectors: A comparative study

Abstract: Speech recognition with hearing protectors 1 AbstractThe perceived negative influence of standard hearing protectors on communication is a common argument for not wearing them. Thus, 'augmented' protectors have been developed to improve speech intelligibility. Nevertheless, their actual benefit remains a point of concern.In this paper, speech perception with active earplugs is compared to standard custom-made earplugs. The two types of active protectors included amplify the incoming sound respectively with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Wearers should listen to ambient sounds through the devices while they adjust them and recognize that they can make additional output adjustments as the ambient noise changes. A recent study investigating the benefits of active versus passive hearing protectors has revealed similar results 16 . The results of this study found that speech recognition of active and passive HPDs was highly de pendent on the background noise implemented.…”
Section: Discussionmentioning
confidence: 60%
“…Wearers should listen to ambient sounds through the devices while they adjust them and recognize that they can make additional output adjustments as the ambient noise changes. A recent study investigating the benefits of active versus passive hearing protectors has revealed similar results 16 . The results of this study found that speech recognition of active and passive HPDs was highly de pendent on the background noise implemented.…”
Section: Discussionmentioning
confidence: 60%
“…A value that gives confidence to users that all critical communications will be understood would seem more desirable. The approach adopted here of optimizing speech SNR in separate subbands while avoiding signal compression eliminates the possibility of introducing electronic distortion that could compromise intelligibility (Bockstael et al, 2011). Moreover, a subband approach could be extended to persons with mild hearing loss, who could benefit from increased speech SNR (Plomp, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Most solutions have attempted to increase the speech signal-to-noise ratio (SNR) either directly or by influencing the upward spread of masking (Rankovic et al, 1992;Schwander and Levitt, 1987;Shields and Campbell, 2001;van Dijkhuizen et al, 1991). Understanding speech when wearing a communication headset/hearing protector (HPD) in a noisy environment introduces additional considerations (Abel et al, 2011;Bockstael et al, 2011;Giguère et al, 2011). There are two typical but fundamentally different situations.…”
Section: Introductionmentioning
confidence: 98%
“…As these are levels at the eardrum, which would have to undergo head-related transfer functions in order to scale them to free-space levels, these values are not directly comparable to directives for safe sound exposure levels which are all set for free/diffuse field exposure (Hammershøi and Møller 2008). However, for speech, the difference between in-ear and free-field levels can be estimated to be around 6 dB based on previous work with a similar measurement setup (Bockstael et al 2011). Based on this conversion, exposure levels fully complied with the 85 dB(A) level deemed to be safe for 8-hours exposure according to the European Directive for occupational noise exposure ("Directive 2003-10-EC on the Minimum Health and Safety Requirements Regarding the Exposure of Workers to the Risks Arising from Physical Agents (Noise)" 2003).…”
Section: Speech Intelligibility and Sound Exposurementioning
confidence: 99%
“…This would de facto result in a more advantageous signal-to-noise ratio at the side where the phone was held, because that ear is much more shielded from the background noise than the contralateral ear. In addition, it is known that a clear separation between signal and noise (one ear predominantly exposed to the noise, the other predominantly exposed to speech) improves speech intelligibility (Bockstael et al 2011). Especially in highest levels of background noise (car), shielding and spatial separation would have the most distinct effect and improve speech intelligibility scores.…”
Section: Simultaneous Exposure To Rf-emf and Sound Pressurementioning
confidence: 99%